Type specimens of Coenosiini (Diptera, Muscidae) deposited in the Museum für Naturkunde, Humboldt-Universität zu Berlin (Berlin, Germany) - Couri, Márcia S.; Pont, Adrian C. (Zootaxa, 2020)
The Museum für Naturkunde of the Humboldt-Universität zu Berlin houses one of the most important and extensive collections of Muscidae (Diptera) in Europe as it includes more than 700 species described by Paul Stein and many others described by two other European dipterists, F. H. Loew and T. Becker. The relevance of the collection is even greater due to the excellent geographic coverage of this material. In this paper, we give a morphological and taxonomic revision of the 114 types of Coenosiini deposited in this collection. Differential diagnoses, notes on the types and photographs of some of them (habitus and labels) are provided.